Acute postsurgical suppurative parotitis: current prevalence at Hospital das Clínicas, São Paulo University Medical School Parotidite aguda pós-cirúgica: prevalência atual no Hospital das Clínicas da Faculdade de Medicina da Universidade de São Paulo - Sergio Quilici Belczak; Roberto de Cleva; Edivaldo M. Utiyama; Ivan Cecconello; Samir Rasslan; José Gustavo Parreira (Revista do Instituto de Medicina Tropical de São Paulo, 2008)
Postsurgical acute suppurative parotitis is a bacterial gland infection that occurs from a few days up to some weeks after abdominal surgical procedures. In this study, the authors analyze the prevalence of this complication in Hospital das Clínicas/São Paulo University Medical School by prospectively reviewing the charts of patients who underwent surgeries performed by the gastroenterological and general surgery staff from 1980 to 2005. Diagnosis of parotitis or sialoadenitis was analyzed. Sialolithiasis and chronic parotitis previous to hospitalization were exclusion criteria. In a total of 100,679 surgeries, 256 patients were diagnosed with parotitis or sialoadenitis. Nevertheless, only three cases of acute postsurgical suppurative parotitis associated with the surgery were identified giving an incidence of 0.0028%. All patients presented with risk factors such as malnutrition, immunosuppression, prolonged immobilization and dehydration. In the past, acute postsurgical suppurative parotitis was a relatively common complication after major abdominal surgeries. Its incidence decreased as a consequence of the improvement of perioperative antibiotic therapy and postoperative support. In spite of the current low incidence, we believe it is important to identify risks and diagnose as quick as possible, in order to introduce prompt and appropriate therapeutic measures and avoid potentially fatal complications with the evolution of the disease. A parotidite supurativa pós-cirúrgica é infecção bacteriana da glândula que ocorre poucos dias até algumas semanas após procedimento cirúrgico. Os autores analisam a prevalência desta complicação cirúrgica nos últimos 25 anos do Hospital das Clínicas de São Paulo. Foram analisados os prontuários das cirurgias realizadas pelos serviços de Cirurgia do Aparelho Digestivo e Cirurgia Geral da Faculdade de Medicina da Universidade de São Paulo no período de 1980 a 2005, num total de 106790 cirurgias. Todos os prontuários que apresentaram entre os diagnósticos das altas complicações cirúrgicas, parotidite ou sialoadenite foram avaliados. Foram identificados 256 prontuários. Pacientes com outras complicações, ou que já apresentavam sialolitíase ou parotidite crônica anterior à internação foram excluídos do estudo. Foram identificados apenas três casos de parotidite aguda supurativa pós-cirúrgica, revelando incidência de 0,0028%. A parotidite supurativa pós-cirúrgica foi complicação relativamente comum de grandes cirurgias abdominais no passado, com acentuada redução atual da sua incidência decorrente da antibioticoterapia de amplo espectro, além de preparação pré-operatória adequada e suporte pós-operatório dos pacientes. Apesar da baixa incidência atual, consideramos importante identificar seus fatores de risco, assim como realizar diagnóstico precoce, conduta terapêutica apropriada para evitar complicações letais associadas a esta infecção.